Analysis of Students' Cognitive Abilities Based on Gender and Learning Style - Bayyinah Rismawati; Hadi Kusmanto; Hendri Handoko (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to determine the differences in students' cognitive abilities based on gender and the influence of learning styles on cognitive abilities. Using a quantitative method with a One Shot Case Study design, the study involved 40 students of grade VIII MTsN 2 Cirebon. Data were collected through questionnaires and tests, then analyzed descriptively, sample independent t-tests, and simple linear regressions. The results showed that there was a difference in the average cognitive ability between male and female students. The average score of male cognitive ability is 85% and is in the high category. The average cognitive ability of students with visual, auditory, and kinesthetic learning styles is in the moderate category of around 65-66%. In addition, auditory learning styles have the highest influence on students' cognitive abilities, followed by visual and then kinesthetic learning styles.